Selection and Estimation the Genetic Parameters of Rootstock Characteristics on Cocoa Seedling of Half-sibs Families - Agung Wahyu Susilo; Dyah Sulastri; Soeboer Djatiwaloejo (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2005)
For cocoa clonal propagation it need rootstock with good characteristics. Half sibs families is the most appropriate alternative for rootstock selection. This study was aimed to select and estimate genetic parameters of cocoa seedling on the half sibs families of DR 1, DR 2, ICS 60, DRC 15, BLC 4, DRC 16, KEE 2, ICS 13, KW 162, KW 163, PA 300, RCC 70, TSH 858, Sca 6 and Sca 12. Research was carried out in Kaliwining Experimental Station of Indonesian Coffee and Cocoa Research Institute. Genetic parameter were estimated based on variance and covariance component of the variables of the number of leaf, stem height, stem girth, leaf acreage, the volume of fresh root, the length of secondary root and the length of primary root which assessed along seed growth till 90 day after planting. The result showed that most of the recorded variables perform high category of narrow sense heritability (h 2>0.5). Stem girth, leaf acreage, volume of fresh root, length of secondary root and the length of primary root were assessed as the broad category of genetic variability (d2 A >2Sed 2 A ). Therefore, length of primary root and length of secondary root would be the main criterion for rootstock selection as their performance on broad category of genetic variability and high category of narrow sense heritability. Length of secondary root can be estimated based on the performance of stem girth (r = 0.5 * ) and leaf acreage (r = 0.23*) and the primary root can be stimated based on the performance of stem height (r = 0.81 * ) and leaf acreage (r = 0.72*). Based on positive selection of primary root lenght and negative selection of secondary root lenght it was identified that the families of KEE 2 and Sca 12 potentially would be good rootstock due to their long category of the primary root and short category of the secondary root that having characteristics of high water uptake and low vigor. Key words: selection, genetic parameter, half-sib familiy, rootstock, cocoa.